Factors Affecting Senior High School Students' Willingness to Communicate in English in the EFL Classroom - Ervin Candra Hari Andika; Aan Erlyana Fardhani; Eka Wahjuningsih (EFL Education Journal, 2022)
This study aims at revealing factors affecting senior high school students’ willingness to communicate (WTC) in English in the classroom. This study employed a descriptive research design, and was situated in an Indonesian state senior high school in Sumenep, Madura. The data were collected from 57 students by using an adapted questionnaire taken from Riasati & Rahimi (2018), and the result was analyzed using descriptive statistics. The findings revealed that the students’ WTC in English in class were affected by both individual and situational factors. The individual factors here include L2 self-confidence, L2 self-perceived communication competence, L2 anxiety, and fear of making mistakes. Meanwhile, the situational factors consist of task types, interlocutors’ effects, topics of discussion, and seating locations. Thus, it was suggested that the English teachers should not only encourage the students’ self-confidence in speaking English, or convince them that making mistakes is part of learning, but also should be careful in deciding the type of task given, topic to be discussed, and even the seating arrangements for their students, since all of these affect the students’ WTC in English in class.